Mg-, Zn-, and Fe-Based Alloys With Antibacterial Properties as Orthopedic Implant Materials - Wang, Ning; Ma, Yutong; Shi, Huixin; Song, Yiping; Guo, Shu; Yang, Shude (Frontiers in Bioengineering and Biotechnology, 2022)
Implant-associated infections (IAI) are one of the major challenges in orthopedic surgery. The development of implants with inherent antibacterial properties is an effective strategy with which to resolve this issue. In recent years, biodegradable alloy materials have received considerable attention because of the superior comprehensive performance in the field of orthopedic implants. Studies on biodegradable alloy orthopedic implants with antibacterial properties have gradually increased. This review summarizes the recent advances on biodegradable Mg-based alloys, Fe-based alloys and Zn-based alloys with antibacterial properties as orthopedic implant materials. The antibacterial mechanisms of these alloy materials are also outlined, thus providing more basis and insights on design and application for biodegradable alloys with antibacterial properties as orthopedic implants.